Opportunities for predicting adverse pregnancy outcomes in severe COVID-19 - V. F. Bezhenar; I. A. Dobrovolskaya; I. M. Nesterov; A. V. Schegolev; A. N. Kucheryavenko; S. G. Meshchaninova; V. S. Pakin; A. A. Nikulin (IRBIS LLC, 2023)
Aim: to asses an opportunity for predicting an unfavorable perinatal and maternal pregnancy outcome in severe novel coronavirus infection (NCI) COVID-19.  Materials and Methods. A retrospective comparative study of the course and outcomes of pregnancies was performed in 40 patients with a gestational age of 22-42 weeks who had severe and extremely severe COVID-19 in 2021. The main group included 21 cases with an extremely severe course of the disease resulting in maternal mortality; the comparison group consisted of 19 patients with severe COVID-19 who successfully completed pregnancy. The diagnosis of NCI COVID-19 was confirmed in all cases by identifying SARS-CoV-2 RNA by polymerase chain reaction in a nasopharyngeal swab. During the study, all patients (during hospitalization, at the peak of the disease and before death/discharge from the hospital) underwent a comprehensive anamnestic, clinical and laboratory-instrumental examination. There were analyzed clinical blood test, biochemical parameters - lactate dehydrogenase (LDH), alanine aminotransferase, aspartate aminotransferase, creatinine, glucose, total bilirubin, total protein; coagulation parameters - prothrombin level according to Quick and fibrinogen, activated partial thromboplastin time, international normalized ratio; the level of C-reactive protein, procalcitonin, D-dimer, interleukin-6 (IL-6); ultrasound examination was performed during pregnancy (fetometry, placentometry), dopplerometry of uteroplacental blood flow and ultrasound of the pelvic organs, as well as pathomorphological placenta examination.  Results. In patients who died from extremely severe NCI COVID-19 (main group), the course of the infection was accompanied by developing of respiratory distress (RD) degree III (χ2 = 12.84; p ≤ 0.05), and a progressive deterioration in mother's condition and/or fetal distress was an indication for emergency delivery by caesarean section (CS). The course of severe NCI COVID-19 in patients with a favorable outcome (comparison group), as a rule, was accompanied by the development of RD grade I and/or II; most of them were also delivered by CS on an emergency/urgent basis. Predictors of rapid progression of severe NCI COVID-19 in the main group were identified: subfebrile body temperature at the initial stages skewing to high fever during treatment instead of rapid temperature normalization (χ2 = 5.41; p ≤ 0.05; odds ratio (OR) = 5.0; 95 % confidence interval (CI) = 1.23-20.3); lack of leukocytosis at the initial stages (χ2 = 4.91; p ≤ 0.05; OR = 50; 95 % CI = 5.43-460.54) with rapidly increased leukocyte count with persistent stagnation in dynamics until death (χ2 = 19.79, p ≤ 0.05, OR = 50; 95 % CI = 5.43-460.54); severe lymphopenia (χ2 = 8.09; p ≤ 0.05; OR = 7.29; 95 % CI = 1.74-30.56), neutrophilia (χ2 = 10.17; p ≤ 0.05; OR = 10.29; 95 % CI = 2.21-47.84); high LDH values (χ2 = 17.99; p ≤ 0.05; OR = 31.88; 95 % CI = 5.09-199.49); increased IL-6 level at the peak of the disease (χ2 = 9.66; p ≤ 0.05; OR = 18; 95 % CI = 1.99-162.62) and in dynamics, as well as stably high D-dimer values (χ2 = 9.53, p ≤ 0.05; OR = 11.33; 95 % CI = 2.07-62.11).  Conclusion. Significant changes observed in clinical and laboratory examination were identified, which reliably reflect the degree of patients' state, to be interpreted as predictors of adverse pregnancy outcomes during NCI COVID-19 and as a potentially justified serious reason for making a decision in the light of timely delivery aimed at a favorable outcome for mother and child. Timely delivery, carried out within the time limits for enabling adequate compensatory capabilities of the pregnant woman's body, demonstrates a rapid normalization of the main laboratory parameters.